Thermal tolerance of the coffee berry borer Hypothenemus hampei: predictions of climate change impact on a tropical insect pest. - Juliana Jaramillo; Adenirin Chabi-Olaye; Charles Kamonjo; Alvaro Jaramillo; Fernando E Vega; Hans-Michael Poehling; Christian Borgemeister (PLoS ONE, 2009)
Coffee is predicted to be severely affected by climate change. We determined the thermal tolerance of the coffee berry borer, Hypothenemus hampei, the most devastating pest of coffee worldwide, and make inferences on the possible effects of climate change using climatic data from Colombia, Kenya, Tanzania, and Ethiopia. For this, the effect of eight temperature regimes (15, 20, 23, 25, 27, 30, 33 and 35 degrees C) on the bionomics of H. hampei was studied. Successful egg to adult development occurred between 20-30 degrees C. Using linear regression and a modified Logan model, the lower and upper thresholds for development were estimated at 14.9 and 32 degrees C, respectively. In Kenya and Colombia, the number of pest generations per year was considerably and positively correlated with the warming tolerance. Analysing 32 years of climatic data from Jimma (Ethiopia) revealed that before 1984 it was too cold for H. hampei to complete even one generation per year, but thereafter, because of rising temperatures in the area, 1-2 generations per year/coffee season could be completed. Calculated data on warming tolerance and thermal safety margins of H. hampei for the three East African locations showed considerably high variability compared to the Colombian site. The model indicates that for every 1 degrees C rise in thermal optimum (T(opt.)), the maximum intrinsic rate of increase (r(max)) will increase by an average of 8.5%. The effects of climate change on the further range of H. hampei distribution and possible adaption strategies are discussed. Abstracts in Spanish and French are provided as supplementary material Abstract S1 and Abstract S2.